Numbers for Boys and Words for Girls? Academic Gender Stereotypes among Chinese Parents. - Li, Jing; Faisal, Eman; Al Hariri, Ahmed (Sex Roles, 2022)
Academic gender stereotypes contribute to observed gender differences in educational enrollment and attainment. Investigating parents' stereotypes among 907 families in China, this study used exploratory and confirmatory factor analyses to uncover four latent factors: boys-Math, boys-Sciences, girls-Chinese, and girls-Liberal Arts stereotypes. The former two depicted boys as more gifted, enthusiastic, and higher-achieving learners in Math and Sciences, and the latter two favored girls in Chinese and Liberal Arts. This four-factor structure was invariant across parents with sons and daughters after accounting for the nonindependence of parents within families. The boys-Math and boys-Sciences stereotypes were found to be stronger than the other two stereotypes. Further analyses revealed nuances concerning the boys-Math stereotype: it was more pronounced among mothers than fathers in families with daughters, fathers with sons than daughters, and girls' mothers without college degrees than those with degrees. Within the same family, mothers more commonly held stereotype-consistent perceptions concerning Math and Chinese than fathers, but there was a general agreement over gendered perceptions of all four achievement domains regardless of child gender. The findings highlight the need for family-based awareness-raising programs targeting parents' gender stereotypes to create gender-fair and gender-inclusive learning environments.